Babesia duncani as a Model Organism to Study the Development, Virulence, and Drug Susceptibility of Intraerythrocytic Parasites In Vitro and In Vivo . (4th May 2022) - Pal, Anasuya C; Renard, Isaline; Singh, Pallavi; Vydyam, Pratap; Chiu, Joy E; Pou, Sovitj; Winter, Rolf W; Dodean, Rozalia; Frueh, Lisa; Nilsen, Aaron C; Riscoe, Michael K; Doggett, J Stone; et al.
Abstract: Human babesiosis is a malaria-like illness caused by tick-borne intraerythrocytic Babesia parasites of the Apicomplexa phylum. Whereas several species of Babesia can cause severe disease in humans, the ability to propagate Babesia duncani both in vitro in human erythrocytes and in mice makes it a unique pathogen to study Babesia biology and pathogenesis. Here we report an optimized B. duncani in culture–in mouse (ICIM) model that combines continuous in vitro culture of the parasite with a precise model of lethal infection in mice. We demonstrate that B. duncani –infected erythrocytes as well as free merozoites can cause lethal infection in C3H/HeJ mice. Highly reproducible parasitemia and survival outcomes could be established using specific parasite loads in different mouse genetic backgrounds. Using the ICIM model, we discovered 2 new endochin-like quinolone prodrugs (ELQ-331 and ELQ-468) that alone or in combination with atovaquone are highly efficacious against B. duncani and Babesia microti . Abstract : We describe an optimized Babesia duncani in culture–in mouse model that combines continuous parasite replication in human erythrocytes and lethal infection in mice. Study findings support the use of this model to study Babesia virulence and develop new therapies for human babesiosis.